Critics and Suggestions for GPO in Science Teaching a Free Online Resource for Teachers in Indonesia Implemented by Universitas Terbuka - Surachman Dimyati; . Mujadi (Bandar Lampung University (UBL), 2014)
Science should be taught in certain ways in order to lead and encourage students to get the optimum results in education. The use of best practices in teaching, especially in teaching science in the mode of streaming has been implemented in Universitas Terbuka not only for its students but also for all of the teachers in Indonesia and around the world. A survey of the Guru Pintar Online (GPO) products with a number of experts was conducted to get the issues how to improve the contents and the techniques the online teacher resources.The GPO is an outstanding resource especially for teachers who deserve the results for their students in understanding science and other subject matters. There were three main issues need to be improved, such as limitation the introduction by the presenter, the use of the appropriate material to focus to the concepts promoted, and some new techniques to minimize the high resolution of the internet connections.Some examples of the GPO products were played, observed, and discussed. Other international best practices streaming teaching products were also played, observed and discussed. Some findings to improve the GPO products need to be implemented was the most important issues in this survey.